DISKRESI KEPOLISIAN DALAM PENGGUNAAN SENJATA API PADA PROSES PENANGKAPAN TERSANGKA TINDAK PIDANA CURANMOR (Studi Kasus di Satreskrim Polresta Padang) - Yuliadi Yuliadi (UNES Journal of Swara Justisia, 2018)
The Police is one of the law enforcement agencies that has the power, power andauthority to perform the Police Discretion in the use of firearms in arrest of the suspect asset forth in Article 18 paragraph (1) and paragraph (2) of Law Number 2 Year 2002regarding Police Republic of Indonesia. Discretion of the police in the use of firearms inarresting suspects is the most recent action taken to paralyze a suspect. The issuesdiscussed in this thesis are: 1) Is the basis of consideration of Polri members to conductpolice discretion in the use of firearms in arrest of suspect crime? 2) How is theimplementation of police discretion in the use of firearms in the arrest of suspectedcriminal offenses in Padang Police? 3) What is the form of supervision and accountabilityfor the use of firearms by members of the National Police in Padang Police?. Thisresearch is descriptive analysis that describes or describes and explains the object ofresearch in a complete, clear and objective manner that has to do with the problem. Theapproach method used in this research is the normative juridical approach as the mainand empirical juridical approach as supporting the main approach, while the type of dataused includes primary data and secondary data. From the results of research anddiscussion can be concluded that: first, the rationale juridical discretion of the policeagainst the Law No.2 of 2002 on the Police of the Republic of Indonesia and Perkap No.1Year 2009 on the Use of Police Violence Collapse. Secondly, the implementation of thePolice Discretion is conducted in a situation that is very necessary and helps to investigateand make efforts against the police.. Third, supervision and accountability of the policediscretion in Padang Polresta directly to the leader or supervisor of the privacy. It isexpected that the government and internal police to reinforce existing regulations andequip facilities and infrastructure of the police